Related Board Diversity and Firm Value - Makaryanawati, Makaryanawati; Azzardina, Aulia; Haslinda, Haslinda (International Journal of Business, Law, and Education, 2024)
This study aims to examine the effect of board diversity in the form of tenure, level of education and expertise on firm value. The sample in this study used property, real estate and construction companies listed on the Indonesia Stock Exchange in 2017-2021. Based on the results of purposive sampling, 210 companies were obtained that met the sample criteria. This study used quantitative methods and multiple regression analysis using secondary data in the form of annual reports and financial reports available on the Indonesia Stock Exchange. The results of hypothesis testing show that the diversity of board experience has a positive effect on firm value while the diversity of tenure and education level of the board of directors has no effect on firm value. The findings of this study can be used by companies in establishing good corporate governance to improve company performance and investor confidence